Pengaruh Pelapisan Nanopartikel Kitosan terhadap Karakter Fisiko-Kimia dan Sensoris Pascapanen Buah Jeruk Siam (Citrus nobilis) - Welther Albettha Sembiring; I Made Supartha Utama; I Wayan Widia; Ni Made Defy Janurianti (Jurnal BETA (Biosistem dan Teknik Pertanian), 2024)
Siamese O range ( C itrus nobilis ) is one of the best known fruits in Indonesia and is quite resilient to spoilage ; therefore, one approach that is being taken is the use of an edible coating with chitosan nanoparticle coating material to help prevent damage and extend the shelf life of the fruit. This research aims to determine the effect of chitosan nanoparticles an d to obtain the best concentration as a coating material on the physico - chemical and sensory characteristics of Siam orange during its post - harvest period. This study used a Completely Randomized Design (CRD) with five concentration levels: 0% (E0), 0.2% ( E1), 0.4% (E2), 0.8% (E3), and 1% (E4), with three repetitions, resulting in 15 experimental units. The physico - chemical parameters observed include weight loss, color difference, fruit density, total soluble solids (TSS), and total acid content, as well a s sensory attributes such as sweetness and aroma of the fruit. The results of this study . showed that the application of chitosan nanoparticles significantly affected weight loss, color difference, total soluble solids, total acid content, and sensory test s of Siam orange during the post - harvest period. Fruit coating with a concentration of 0.4% (E2) was the best concentration with an average weight loss of 3.5%, an average total soluble solids of 11.7% Brix, and the highest sensory value for fruit flavor w ith an average score of 3.5. Fruit coating with a concentration of 0.2% (E1) achieved the best results in color difference at 50.9, while fruit coating with a concentration of 1% achieved the best results in total acid content with a value of 2.3%.